Association of high-density lipoprotein subclasses and incident coronary heart disease: The Jackson Heart and Framingham Offspring Cohort Studies. (29th August 2020) - Joshi, Parag H; Toth, Peter P; Lirette, Seth T; Griswold, Michael E; Massaro, Joseph M; Martin, Seth S; Blaha, Michael J; Kulkarni, Krishnaji R; Khokhar, Arif A; Correa, Adolfo; D'Agustino, Ralph B; Jones, Steven R
Abstract: Aims: We aimed to clarify the associations of high-density lipoprotein cholesterol (HDL-C) subclasses with incident coronary heart disease (CHD) in two large primary prevention cohorts. Methods: We measured cholesterol at baseline from the two major HDL subfractions (larger, more buoyant HDL2 and smaller, denser HDL3 ) separated by density gradient ultracentrifugation in 4114 (mean age 53.8 years; 64% female) African American participants from the Jackson Heart Study and 818 (mean age 57.3 years, 52% female) predominantly Caucasian participants from the Framingham Offspring Cohort Study. Multivariable adjusted hazard ratios (HRs) for HDL-C and its subclasses were derived from Cox proportional hazards regression models to estimate associations with incident CHD events including myocardial infarction, CHD death, and revascularization. Analyses were performed for each cohort separately and as a combined population. Results: In models adjusted for cardiovascular risk factors for the combined population, HDL3 -C (HR 0.76 per SD increase; 95% confidence interval (CI), 0.62–0.94; p  = 0.01), rather than HDL2 -C (HR 0.88 per SD; 95% CI, 0.72–1.09; p  = 0.24) drove the inverse association of HDL-C (HR 0.79 per SD; 95% CI, 0.64–0.98; p  = 0.03) with CHD. Similar associations were seen in multivariable analyses within each cohort including after adjusting for apolipoprotein A1 in the Jackson Heart Study. Conclusion: Smaller, denser HDL3 -C levels are primarily responsible for the inverse association between HDL-C and incident CHD in this diverse group of primary prevention subjects. These findings have important implications ranging from considerations of HDL biology to interpretations of clinical trials utilizing HDL-C therapeutics.